COMPLEX CLINICAL HOSPITAL MODEL OF DISCHARGE MANAGEMENT: CONCEPTION AND IMPLEMENTATION - Bernardino, Elizabeth; Selleti, Jaqueline Dias do Nascimento; Silva, Otília Beatriz Maciel Da; Gallo, Valéria Cristina Lopes; Silva, Olivia Luciana dos Santos; Rorato, Camila (Cogitare Enfermagem, 2022)
Objective: to present the conception and implementation of the Discharge Management Model of the Clinics Hospital Complex of the Federal University of Paraná. Method: experience report occurred between 2017 and 2020, about the design and implementation of the Discharge Management model with support of the logic model. Results: continuity of care and case management are operationalized by a dedicated team of liaison nurses who manage and counter-reference care to primary care and other points in the health care network. Conclusion: discharge management has been consolidated as a managerial strategy that integrates the health care network, avoids discontinuities in care, promotes patient and family safety, and optimizes beds, and inserts complex patients into the primary care agenda. It contributes to the continuity of care and represents evidence of a new field of work for nurses.